2022
DOI: 10.1109/tcsvt.2021.3074032
|View full text |Cite
|
Sign up to set email alerts
|

Local and Global Perception Generative Adversarial Network for Facial Expression Synthesis

Abstract: Facial expression synthesis has gained increasing attention with the development of Generative Adversarial Networks (GANs). However, it is still very challenging to generate high-quality facial expressions since the overlapping and blur commonly appear in the generated facial images especially in the regions with rich facial features such as eye and mouth. Generally, existing methods mainly consider the face as a whole in facial expression synthesis without paying specific attention to the characteristics of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Other studies explore methods for applying high-fidelity motion to those virtual avatars to make them seemingly move actual humans. Motion recognition [57], motion tracking [58] and motion caption systems [59] play essential roles in the development of those techniques. Even though most tracking and recognition techniques do not directly transfer motion tracked from real humans to virtual avatars, still, those tracking techniques are qualified resources for applying reference to character motion design and can potentially fill the gap in current motion capture systems.…”
Section: Technical Approachesmentioning
confidence: 99%
“…Other studies explore methods for applying high-fidelity motion to those virtual avatars to make them seemingly move actual humans. Motion recognition [57], motion tracking [58] and motion caption systems [59] play essential roles in the development of those techniques. Even though most tracking and recognition techniques do not directly transfer motion tracked from real humans to virtual avatars, still, those tracking techniques are qualified resources for applying reference to character motion design and can potentially fill the gap in current motion capture systems.…”
Section: Technical Approachesmentioning
confidence: 99%
“…GANs have proven successful for face-related tasks including facial attribute editing [3], [4], [5], [6] and face super-resolution [7], [8], [9], [10]. A substantial amount of work has also been done in the area of facial expression synthesis with the prevalence of GANs such as StarGAN [11], GANimation [12], Cascade-EF GAN [13], DAI2I [14] and LGP-GAN [15]. However, most of these methods including StarGAN, GANimation, Cascade-EF GAN and DAI2I need large training datasets.…”
Section: Introductionmentioning
confidence: 99%
“…When the main direction of the gesture obtained was inconsistent with the main direction of similar gestures in the training library, it was prone to error recognition. In view of the complexity of current gesture feature extraction methods and the low gesture recognition rate in complex background, the research and practice of references [28,29] found that convolutional neural network (CNN) had scale invariance to flip, pan and scale. It was better than other machine vision methods in gesture detection and recognition applications.…”
Section: Introductionmentioning
confidence: 99%